To evaluate the equation \( y = 5 + 3x - 7 - 2x \) for \( x = 2 \) and \( x = 5 \), we will first substitute the x-values into the equation without simplifying.
Step 1: Plug in \( x = 2 \)
Substituting \( x = 2 \) into the equation:
\[ y = 5 + 3(2) - 7 - 2(2) \]
Step 2: Plug in \( x = 5 \)
Now, substituting \( x = 5 \):
\[ y = 5 + 3(5) - 7 - 2(5) \]
Step 3: Evaluate
Now we will evaluate both expressions.
- For \( x = 2 \):
\[ y = 5 + 3(2) - 7 - 2(2) \] \[ = 5 + 6 - 7 - 4 \] \[ = 5 + 6 - 7 - 4 = 0 \]
So, when \( x = 2 \), \( y = 0 \).
- For \( x = 5 \):
\[ y = 5 + 3(5) - 7 - 2(5) \] \[ = 5 + 15 - 7 - 10 \] \[ = 5 + 15 - 7 - 10 = 3 \]
So, when \( x = 5 \), \( y = 3 \).
Summary of Results
- For \( x = 2 \), \( y = 0 \)
- For \( x = 5 \), \( y = 3 \)